Analysis of Weed Vegetation on Ex-Burned Oil Palm Plantation Land - Arief Rahman; Muhammad Mariadi Wahid; Andi Lelanovita; Humairo Aziza; Sukariyan Sukariyan; Suparno Suparno (Poltanesa, 2025)
Weeds frequently present challenges in agricultural settings, leading to crop damage and diminished yields.  The size of the current weed population is often closely linked to these issues.  The primary factor at play is the competition between crops and weeds for space, nutrients, and light essential for growth.  Given that weeds are considered undesirable, their control represents a significant area of focus.  A method to assess effective weed control strategies involves vegetation analysis, offering insights into weed distribution and density.  The data aids in formulating an effective control strategy to reduce the adverse effects of weeds on oil palm yield. This investigation seeks to analyze the composition and structure of weeds, as well as evaluate the efficacy of weed control measures on ex-burned land.  This study employs field surveys to catalog the types and quantities of individual weeds, alongside vegetation analysis to assess weed structure through relative density, frequency, and dominance metrics. The findings revealed a total of 275 distinct weed compositions, encompassing 15 species across 10 families.  The prevalent weed species identified included Eleocharis dulcis, Paspalum conjugatum, and Fimbristylis miliacea.  The density, frequency, and dominance values of these three weeds were notably high.  The weed diversity index in the peatland was measured at 2.13, indicating a high classification.  The approach to weed management involves an integration of both physical and chemical techniques.